Strategi Komunikasi Bank Indonesia Provinsi Bali dalam Mensosialisasikan Sistem Pembayaran QRIS di Pasar Badung Bali - Prasetya, Karinka Bella; Suryawati, I Gusti Agung Alit; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium; Vol 3 No 2 (2022): Jurnal Ilmu Komunikasi Vol 3 No 2 Tahun 2022, 2023)
This study aims to provide an overview and explanation regarding the communication strategy carried out by Bank Indonesia Bali Province in disseminating the QRIS payment system to the public, especially traders and buyers at Badung Market. This study uses qualitative research methods using data collection techniques in the form of observation, interviews, and document studies. Based on the research that has been done, the results show that Bank Indonesia Bali Province in socializing the QRIS payment system at the Badung Market uses four steps in developing a communication strategy, namely knowing the audience, compiling messages, determining methods, and selecting the use of media to be used. Bank Indonesia also utilizes new media, outdoor media, and special events to convey the message of the QRIS payment system to the public at the Badung Market. Keywords: Communication Strategy, Public Relation, Socialization, Bank Indonesia, QRIS.